2013
DOI: 10.1016/j.ympev.2012.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the western South Atlantic Sciaenidae based on mitochondrial and nuclear data

Abstract: Fragments of mitochondrial (COI and rRNA 16S) and nuclear (Tmo-4C4) genes were sequenced to evaluate the phylogenetic relationships among 15 genera of the western South Atlantic Sciaenidae, two freshwater genera and the northwest Pacific Larimichthys crocea. Our results suggest a great diversification for the western Atlantic assemblage; the monophyly of Macrodon, Menticirrhus and Plagioscion genera; the distinctiveness of Bardiella, Stellifer and Ophioscion as belonging to the same clade; the possible existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
21
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 20 publications
8
21
2
1
Order By: Relevance
“…2). This study and previous 358 molecular studies (Vinson et al, 2004;Vergara-Chen et al, 2009;Santos et al, 2013) 359 reject the hypothesis of the monophyly of Cynoscion based on morphology (Chao, 360 1978;Sasaki, 1989). 361…”
Section: Habitat Preference Evolution 314supporting
confidence: 67%
See 1 more Smart Citation
“…2). This study and previous 358 molecular studies (Vinson et al, 2004;Vergara-Chen et al, 2009;Santos et al, 2013) 359 reject the hypothesis of the monophyly of Cynoscion based on morphology (Chao, 360 1978;Sasaki, 1989). 361…”
Section: Habitat Preference Evolution 314supporting
confidence: 67%
“…2). The 428 18 18 present study confirms the monophyly of the genus Menticirrhus (with two species 429 sampled)(Chao, 1978;Vinson et al, 2004;Santos et al, 2013) with strong support. 430Lineage 11 is the largest lineage (22 genera included) and it can be subdivided 431 into four clades (A-D) although the relationships among these clades are not resolved 432(Fig.…”
supporting
confidence: 70%
“…In a recent study based on both mitochondrial (COI and 16S rRNA) and nuclear markers (TMO-4C4), Santos et al [17] concluded that Stellifer is a sister group of Ophioscion and that Bairdiella is the basal taxon within the group, confirming the proposal of Sasaki [1]. However, as in Vinson et al [16], the relationships between all of the taxa of the Stellifer group could not be defined because Odontoscion was not included in the analyses.…”
Section: Introductionmentioning
confidence: 95%
“…Despite this, few studies have focused on the bio-ecological or phylogenetic characteristics of this group. Regarding the phylogenetic relationships, all the available studies [1], [5], [16], [17] have emphasized the close relationships among Bairdiella, Stellifer, Ophioscion , and Odontoscion , although intergeneric and interspecific relationships have yet to be defined conclusively due to the limitations or inconsistencies found in the data, as described below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation